Hereditary haemorrhagic telangiectasia: a clinical analysis. - Porteous, M E (J Med Genet, 1992)
Data from 98 patients with hereditary haemorrhagic telangiectasia (HHT) are presented. All were symptomatic by 40 years of age and 62% by 16 years. Nose bleeding was the first symptom of disease in 90% of cases with mucocutaneous telangiectases appearing 5 to 20 years later. Complications of HHT are discussed and an age of onset curve given. IMAGES: